Non-microbial food poisoning : methodical recommendations to prepare 3rd year students for practical classes Discipline "Hygiene and ecology" [Electronic resource] - Redka, Iryna Vasilyivna; Редька, Ірина Василівна (Kharkiv : V.N. Karazin Kharkiv National University, 2023)
Methodological recommendations highlight the pathogenesis, symptoms and prevention of the most common types of food poisoning of anon-microbial nature, such as: poisoning by mushrooms, wild plants, weed seeds, vegetables, fruits and products of animal origin that acquire the properties of toxicity under certain conditions, seafood and shellfish. Particular attention is paid to poisoning caused by pesticide residues in food and chemical impurities that migrate into food from cooking utensils or packaging materials. Methodical recommendations contain theoretical material, test questions for self-control, situational problems for independent solution, a list of modern recommended literature.

Методичні рекомендації висвітлюють патогенез, симптоматику та профілактику найпоширеніших видів харчових отруєнь немікробної природи, такі як: отруєння грибами, дикорослими рослинами, насінням бур’янів, овочами, фруктами та продуктами тваринного походження, що набувають властивості токсичності за певних умов, морепродуктами та молюсками. Окрема увага приділена отруєнням, зумовлених залишками пестицидів у продуктах харчування та хімічних домішок, які мігрують до продуктів харчування з посуду для приготування їжі або пакувальних матеріалів. Методичні рекомендації містять теоретичний матеріал, тестові питання для самоконтролю, ситуаційні задачі для самостійного розв`язання, список сучасної рекомендованої літератури.
Немікробні харчові отруєння: методичні рекомендації до підготовки студентів 3 курсу до практичних занять з дисципліни "Гігієна та екологія" [Електронний ресурс]
Methodical recommendations
Keywords: MEDICINE; FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; NATURAL SCIENCES; food poisoning; poisonous mushrooms; conditionally edible mushrooms; ciguatera; SCOMBROID; pesticide; heavy metals; цикл азоту; харчове отруєння; отруйні гриби; умовно їстівні гриби; сігуатера; скомброідне отруєння; пестициди; важкі метали